Perception and Resistance Levels of Management Information Systems on University Administrator and Other Staff: A Practice Selcuk University - Sertaç Arı; Esen Şahin (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2018)
In present conditions, the information and communication technology has developed and become popular rapidly. Increasing competition with globalization has been affecting the economic development of the countries. Within that period, a big change has occured both in the organizational structure of the enterprises and also in the business methods of the enterprises. Profit oriented and non-profit businesses' goals include issues such as reducing the costs, increasing the profitability, reducing the need for manpower, effective and rapid decision- making of the management. In order to achieve the goals related with these issues, businesses need on-time information which will guide the decisions to be taken. Production of this information is possible by the existence of the management information systems. However, use of the management information systems actively in business and outside the business accompanies many responsibilities, duties, applications and the new system. On the other hand, the individual exhibits resistance behavior such as rejecting the changes and refusing as the individual thinks that these changes will upset the accustomed order. This study has been carried out in Selcuk University which uses the applications of management information systems actively. Perceptions and resistance levels of the university administrators and university employees against these applications are evaluated comparatively also, resistance reasons of the individuals and the relationships between them were examined. It was also examined whether this relationship is associated with the characteristics such as genders, ages, positions in the organization, education levels, working time and durations of computer use of the employees. In the last part of the study, it was determined that perception and resistance levels of the university administrators and university employees against the management information system depends on which variables and some suggestions were offered